2019
DOI: 10.3171/2018.5.jns18681
|View full text |Cite
|
Sign up to set email alerts
|

Fusiform vertebral artery aneurysms involving the posterior inferior cerebellar artery origin associated with the sole angiographic anterior spinal artery origin: technical case report and treatment paradigm proposal

Abstract: Fusiform aneurysms of the vertebral artery (VA) involving the posterior inferior cerebellar artery (PICA) origin are uncommon and challenging. The anterior spinal artery (ASA) commonly originates from a unilateral ramus just distal to the PICA. Occlusion of an unpaired ASA can result in bilateral medial medullary syndrome. The authors propose a treatment paradigm for ASA preservation based on the artery’s proximity to fusiform VA aneurysms, and they present 3 representative cases. In the first case, they perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The typical ASA originates as a common trunk from paired VAs, and its origin is 5–17 mm proximal to the vertebrobasilar junction, angiographically presenting with a characteristic midline hairpin ( 5 , 9 , 10 ). High anatomical variability of the ASA origin exists, and it often has either a predominance of one ramus over the other or a sole unilateral ramus of origin ( 11 , 12 ). The Santos-Franco et al study reported a less typical bilateral origin of the ASA ( 13 ).…”
Section: Cervical Asa Anatomymentioning
confidence: 99%
See 4 more Smart Citations
“…The typical ASA originates as a common trunk from paired VAs, and its origin is 5–17 mm proximal to the vertebrobasilar junction, angiographically presenting with a characteristic midline hairpin ( 5 , 9 , 10 ). High anatomical variability of the ASA origin exists, and it often has either a predominance of one ramus over the other or a sole unilateral ramus of origin ( 11 , 12 ). The Santos-Franco et al study reported a less typical bilateral origin of the ASA ( 13 ).…”
Section: Cervical Asa Anatomymentioning
confidence: 99%
“…The metal coverage of conventional intracranial stents is low; with their assistance, coiling for VA aneurysms is safe for the ASA ( Figure 5 ) ( 97 ). However, when the ASA originates from the aneurysm, coiling with sacrifice of the ASA should be conducted with caution ( 11 ). If the collateral circulation is insufficient, occlusion of an unpaired ASA can result in bilateral medial medullary syndrome ( 11 , 98 , 99 ).…”
Section: Cervical Asa Ischemia From Asa Occlusion or Coverage By Evtmentioning
confidence: 99%
See 3 more Smart Citations